TGF-β/JNK axis mediates mitochondrial damage and macrophage cGAS-STING activation in liver Mallory-Denk body pathogenesis - Yi Shi; Maoping Huang; Wanmei Zhou; Yi Zhao; Jiuying Zhao; Bei Zhong; Samuel W. French; Xiaoping Tang; Hui Liu (Journal of Translational Medicine)
Abstract Background Mallory-Denk bodies (MDBs) are characteristic proteins and inflammatory aggregates appeared in drug-induced chronic liver injury and various chronic liver disease. MDBs formation is often accompanied with mitochondrial damage and inflammatory environment. However, how mitochondrial damage and inflammatory response affect the pathological process of MDBs is largely unknown. The scope of this study was to provide unprecedented insights into the mechanism of MDBs pathogenesis and the potential target of transforming growth factor beta (TGF-β)/JNK axis in the treatment of MDB-related chronic liver disease. Methods Single-nucleus RNA sequencing (snRNA-seq), typical MDB-related multiplex immunofluorescence staining and functional in vitro and in vivo experiments were performed to investigate the potential mechanisms of TGF-β/JNK axis in the process of MDBs formation in chronic liver injury. Furthermore, the TGF-β/JNK axis has been demonstrated to be activated in clinical patients with metabolic dysfunction-associated steatotic liver disease (MASLD), which implies the potential clinical implications of the TGF-β/JNK axis. Results Our study delineates a hepatocyte-macrophage crosstalk axis wherein TGF-β/TGF-βR dysregulation drives JNK-mediated MDBs pathogenesis. Mechanistically, the activation of JNK pathway upregulates downstream c-JUN expression (p < 0.0009, n = 3) and directly contributes to MDBs formation by promoting transcriptional activation of UbD. Concurrently, JNK signaling promotes BAX/BAK oligomerization, triggering mitochondrial translocation and subsequent generation of mitochondria-derived vesicles (MDVs), as evidenced by the significantly enhanced colocalization between damaged mtDNA and the mitochondrial outer membrane marker TOM20 in the experimental group compared to controls (p = 0.0001, n = 5). Then, following transport to macrophages, mtDNA escapes from MDVs, activating the cGAS-STING signaling and subsequently mediating IL-6 pro-inflammatory cytokine release (p = 0.0006, n = 3). Notably, the inhibition of JNK signaling attenuated both MDBs formation (p = 0.0027, n = 3) and IL-6 secretion (p = 0.0658, n = 3), demonstrating therapeutic potential through dual cytoprotective and immunomodulatory effects. Conclusions This study identifies the novel regulatory mechanism of the TGF-β/JNK signaling axis in MDBs formation, delivering mechanistic insights into MDB-associated chronic liver disease. Inhibition of JNK pathway suppresses MDBs formation while alleviates the inflammatory microenvironment by attenuating mitochondrial damage. Blocking the TGF-β/JNK signaling axis may represent a potential therapeutic strategy for MDB-associated chronic liver disease.